DIVERSIFICATION AS A FACTOR FOR LEVELING THE RISKS OF PRODUCTION AND ECONOMIC ACTIVITY OF AGRICULTURAL ENTERPRISES (INNOVATIVE ECONOMY, 2020)
Svynous I.V., Rudych O.O., Zubchenko V.V. DIVERSIFICATION AS A FACTOR FOR LEVELING THE RISKS OF PRODUCTION AND ECONOMIC ACTIVITY OF AGRICULTURAL ENTERPRISESPurpose. The aim of the article is the development of theoretical, provisions and practical recommendations for development of measures for diversification, as a factor of leveling the production and economic activity of agricultural enterprises.Methodology of research. Modern general scientific and special methods of economic research are used in the article, in particular: a systematic approach – when studying the connections between phenomena and processes in the system of ensuring diversified development; economic and statistical methods – in determining the dynamics, structure and performance of the development of production activities; comparative – in assessing the effectiveness of activities and comparing the levels of diversification of production of agrarian products; calculation and constructive method – in substantiating the directions of diversification of production.Findings. It is proved that the economic expediency of diversification of production activity is determined by its impact on the economic and financial state of the enterprise, as the result of any diversification should be the reduction of risk and the emergence of synergistic effects, especially in the field of finance, due to the possibility of free internal firm transfer of funds in the sphere of activity that develop most dynamically. The estimation of the level of efficiency of agricultural enterprises functioning and the problems identified, which lead to a decrease in the efficiency of their functioning.It is established that the most optimum in terms of efficiency are farms producing 2-3 types of agricultural products, which are part of the branches of livestock and plant production in order to minimize production risks.Originality. The strategy of economic diversification is substantiated based on ensuring an acceptable ratio between profitability and the level of overall risk, which consists of two components: firstly, unsystematic (diversified) risk; it is inherent in a particular enterprise and is subject to a reduction as a result of diversification; and secondly, systematic (not diversified, market) risk; it cannot be reduced by further diversification, since it is generated by external factors of the environment of the functioning of agrarian enterprises.Practical value. The obtained results of the research will help to optimize the structure of production at the enterprise (a rational combination of crop and livestock industries) and ensure the growth of management efficiency on this basis.Key words: agricultural enterprise; diversification; monoculture; uncertainty; economic benefits.
Keywords: Key words; agricultural enterprise; diversification; monoculture; uncertainty; economic benefits.